2022
DOI: 10.1371/journal.pone.0267483
|View full text |Cite|
|
Sign up to set email alerts
|

Maize productivity and soil nutrients variations by the application of vermicompost and biochar

Abstract: Poor soil organic matter is one of the major causes of the deterioration of soil health. Most soils fertility is also decreased when enough organic carbon is not present in the soil. Maize is most susceptible to this poor soil fertility status. A significant amount of maize growth and yield is lost when it is cultivated in low organic matter and poor fertility soil. To overcome this issue organic amendments can play an imperative role. Biochar and vermicompost are organic amendments that can not only improve o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Many researchers have found that, the percentage of protein in the wheat grain had been increased by the addition of biochar fertilizer (Khan et al, 2021). In addition, other researchers have found that the percentages of carbohydrates in wheat grains were also increased by the application of vermicompost and biochar fertilizers (Dawar et al, 2022).…”
Section: Effect Of Fertilizersmentioning
confidence: 99%
“…Many researchers have found that, the percentage of protein in the wheat grain had been increased by the addition of biochar fertilizer (Khan et al, 2021). In addition, other researchers have found that the percentages of carbohydrates in wheat grains were also increased by the application of vermicompost and biochar fertilizers (Dawar et al, 2022).…”
Section: Effect Of Fertilizersmentioning
confidence: 99%
“…This hormone likely stimulates gene expression in chlorophyll biosynthesis and maintenance. Biochar has a high surface area and porous structure that can serve as a substrate for beneficial microorganisms [62][63][64][65]. These microorganisms can contribute to improved nutrient availability, root health, and overall plant performance, including chlorophyll synthesis [66].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have found that the percentage of protein in grain yield of wheat has increased with increasing biochar rates (Khan et al, 2021). In addition, researchers have found that the percentages of carbohydrates in wheat grains were also increased by the application of vermicompost and biochar fertilizers (Dawar et al, 2022). As for vermicompost and biochar fertilizer rates, it is clear from the data in the same Table that gradual and significant increases in phosphorus%, potassium%, crude protein%, and total carbohydrate% have resulted as fertilizer rates increased up to 2400kg/ ha.…”
Section: Grain Qualitymentioning
confidence: 99%